Disentangling site occupancy, cation regulation, and oxidation state regulation of the broadband near infrared emission in a chromium-doped SrGa4O7 phosphor. Issue 12 (11th May 2020) - Lai, Jun'an; Qiu, Jianbei; Wang, Qi; Zhou, Dacheng; Long, Zhangwen; Yang, Yong; Hu, Songhan; Li, Xizheng; Pi, Jiacheng; Wang, Jing
Abstract : The Cr 3+ ions in octahedral sites and the Cr 4+ ions in tetrahedral sites generate unique broadband near infrared emission. Abstract : Cr 3+ -Doped phosphors are attracting attention for broadband near-infrared (NIR) applications. However, some mechanisms are still unclear due to the entangled crystallographic site occupancy and changeable valence of chromium in the host lattice. In this study, a particular gallium SrGa4 O7 (SGO) was employed as a host for chromium doping. The characteristic broadband NIR emission of Cr 3+ ions in octahedral sites centered in the range of 650 to 1200 nm with a full width at half maximum (FWHM) of 140 nm and an internal quantum efficiency of more than 46% was observed, although there were only four and seven coordination sites in the SGO lattice. The distorted octahedron in the SGO lattice was generated due to the transition from Ga–O tetrahedron to the octahedron with the doping of Cr 3+ ions, and it was regulated by the cation regulation of Ca 2+ substituted for Sr 2+ ions in the lattice. In particular, the characteristic Cr 4+ ion emission between 1200 and 1700 nm with an FWHM at ∼215 nm was observed in phosphors for the first time. This study provides new cogitation for the Cr 3+ ion site occupation in the host lattice and a new idea to develop broadband NIR emission phosphors.